Loss of SPECC1L in cranial neural crest cells results in increased hedgehog signaling and frontonasal dysplasia - Tran, An J.; Hufft-Martinez, Brittany M.; Thalman, Dana N.; Maili, Lorena; McKinney, Sean A.; Goering, Jeremy P.; Trainor, Paul A.; Saadi, Irfan (Frontiers in Physiology, 2026)
SPECC1L encodes a cytoskeletal scaffolding protein that interacts with filamentous actin, microtubules, and cell junctional components. In humans, autosomal dominant mutations in SPECC1L cause a syndrome characterized by craniofrontonasal anomalies including broad nasal bridge, ocular hypertelorism, prominent forehead, and cleft lip/palate. Complete loss of SPECC1L in mice on a homogeneous genetic background results in perinatal lethality, accompanied by subtle cranial differences and incompletely penetrant cleft palate. This lethality limits postnatal analysis of craniofacial development. Because cranial neural crest cells (CNCCs) contribute extensively to the formation of anterior craniofacial structures, we investigated whether disruption of SPECC1L in CNCCs contributes to the craniofrontonasal phenotypes observed in SPECC1L-related syndrome. We generated a Specc1l-floxed allele and crossed it with the Wnt1-Cre2 deleter strain, which drives Cre recombinase expression in the dorsal neuroectoderm and NCCs. Most homozygous Specc1lΔCNCC mutants survived postnatally and exhibited hallmark features of the human SPECC1L-related syndrome, including shortened skulls, reduced frontal bone area, nasal defects, and midface hypoplasia. The cranial mesenchyme of Specc1lΔCNCC mice displayed shortened primary cilia and increased Hedgehog (Hh) signaling activity at E13.5, as evidenced by enhanced GLI1 immunostaining. These defects were also observed early in E9.5 facial prominences, indicating that they may drive the adult phenotype. Collectively, Specc1lΔCNCC mice provide a novel model for investigating the roles of CNCCs, primary cilia, and Hh signaling in frontonasal prominence and midfacial development.